2013
DOI: 10.1155/2013/895942
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cysticercosis and Neoplasia: A Study Based on Autopsy Findings

Abstract: Chronic infections including the cysticercosis induce inflammatory cells to produce free radicals and synthesize carcinogenic toxins. The cells with genetic mutations proliferate in a disorganized manner, leading to the development of neoplasia. The aim of the present study was to demonstrate the relation between cysticercosis and neoplasia. Patients autopsied were divided into 4 groups: patients with neoplasia and cysticercosis (NC), patients with neoplasia only (NN), patients with cysticercosis only (CC), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…One study also showed its role in the cardiac dissemination of Chagas disease, a disease linked to Trypanosoma cruzi. Nevertheless, these hypotheses have never been confirmed, even if recent data suggest that a CD20 homolog expressed by tumor-associated macrophages and enhancing tumo-growth could be induced by parasite infection [23,24]. The specific role of taeniasis was studied by Del Brutto et al who observed that 16.8% of patients with a glioma were infected by a neurocysticercosis, which is the larval stage of T. solium [21].…”
Section: Figurementioning
confidence: 99%
“…One study also showed its role in the cardiac dissemination of Chagas disease, a disease linked to Trypanosoma cruzi. Nevertheless, these hypotheses have never been confirmed, even if recent data suggest that a CD20 homolog expressed by tumor-associated macrophages and enhancing tumo-growth could be induced by parasite infection [23,24]. The specific role of taeniasis was studied by Del Brutto et al who observed that 16.8% of patients with a glioma were infected by a neurocysticercosis, which is the larval stage of T. solium [21].…”
Section: Figurementioning
confidence: 99%